2016
DOI: 10.1002/jor.23355
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of distal radioulnar joint ballottement test

Abstract: We investigated the reliability and accuracy of the distal radioulnar joint (DRUJ) ballottement test using five fresh-frozen cadaver specimens in triangular fibrocartilage complex (TFCC)-intact, and TFCC-sectioned wrists. The humerus and proximal ulna were fixed. The ulna was allowed to translate in dorsopalmar directions without rotation, and the radius was allowed to move freely. Four sensors of a magnetic tracking system were attached to the radius and ulna, and the nails of each examiner's thumbs. Five exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…This was in accordance to the conditions in some previous studies. 6,11 These settings enable measurement of the applied force and relative displacement of the ulna-radius. An ultrasound scanner equipped with a linear array transducer was set to a depth of 20 mm.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in accordance to the conditions in some previous studies. 6,11 These settings enable measurement of the applied force and relative displacement of the ulna-radius. An ultrasound scanner equipped with a linear array transducer was set to a depth of 20 mm.…”
Section: Measurementmentioning
confidence: 99%
“…Several methods to quantify the DRUJ displacement have been reported in cadaver studies. [2][3][4][5][6] In addition, several clinical methods with computed tomography (CT) have quantified DRUJ stability, i.e., the radioulnar line method, the subluxation ratio method, the epicenter method and the radioulnar ratio method. [7][8][9][10][11][12] These methods measure radioulnar translation by evaluating the ulnar position relative to the radius position, resulting in a ratio.…”
mentioning
confidence: 99%
“…Exam maneuvers include the piano key test, ulnocarpal stress test, pisiform boost test, press test, DRUJ ballottement, and dynamic examination of the ulnar head with active pronation and supination [41][42][43]. Additional tests, such as a positive ulnar fovea sign, may also indicate ulnotriquetral ligament injury [44].…”
Section: Clinical Exammentioning
confidence: 99%
“…We have conducted several experimental studies to determine the contribution of each ligament to DRUJ stability and to evaluate changes in joint stability in different forearm and wrist positions. 6,50,51 Physiological Dynamic Translation of the Distal Radioulnar Joint…”
Section: Biomechanical Perspectives On Distal Radioulnar Joint Instabmentioning
confidence: 99%
“…Technique A previous biomechanical study using cadaver wrists demonstrated that, compared with other manual stress tests, the DRUJ ballottement test was the most accurate for evaluating instability. 50 The DRUJ ballottement test is usually conducted with the forearm in neutral rotation and is interpreted as positive if the examiner identifies noticeable displacement of the radius relative to the ulnar head or a lack of end-point resistance. Examiners may recognize DRUJ instability depending on the magnitude of movement of the examiner's fingernail grasping the ulnar head and the radius.…”
Section: Technique and Biomechanics Of The Druj Ballottement Testmentioning
confidence: 99%